Peningkatan Keterampilan Proses IPA Menggunakan Metode Eksperimen pada Siswa Kelas VC SD Bantul Timur - Iis Nurfitria Lestari (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2019)
This study aims to improve the science learning process skills using experimental method in grade fifth C of Bantul Timur Elementary School. This type of research is classroom action research grade fifth C of Bantul Timur elementary school. The design of this study is classroom action research according to Kemmis and McTaggart which consists of action planning, action and observation, and reflection. The data were collected using observation. The data were analyzed using quantitative and qualitative descriptive. The results showed by used experimental method in science learning in the first cycle from 68.13% increased to 80.75% in the second cycle. Students who reach minimum value in the first cycle are 13 students or 43% to 27 students or 90% in cycle II.